Women in nineteenth-century Czech musical culture apostles of a brighter future - Bunzel, Anja ca. 20./21.Jh; Campo-Bowen, Christopher (Routledge, Taylor & Francis Group, 2024)
"This volume focuses on the circumstances of women's music-making in the vibrant and diverse environment of the Czech lands during the nineteenth century. It sheds light on little-known women musicians, while also considering more well-known works and composers from new woman-centric perspectives. It shows how the unique environment of Habsburg Central Europe, especially Bohemia and Lower Austria, intersects with gender to reveal hitherto unexplored networks that challenge the methodological nationalism of music studies as well as the discipline's continued emphasis on singular canonical figures. The main areas of enquiry address aspects of performance and identity both within the Czech lands and abroad; women's impact on social life with a view to different private, semi-private, and public contexts and networks; and compositional aesthetics in musical works by and about women, analysed through the lens of piano works, song, choir music, and opera, always with the reception of these works in mind"--
Keywords: Geschichte 1800-1900; Musikerin; Niederösterreich; Tschechien; Music / Czech Republic / 19th century / History and criticism; Music / Social aspects / Czech Republic / History / 19th century; Women musicians / Czech Republic; Musiciennes / République tchèque; Musique / République tchèque / 19e siècle / Histoire et critique; Musique / Aspect social / République tchèque / Histoire / 19e siècle; Music; Music / Social aspects; Women musicians; Czech Republic; 1800-1899; Criticism, interpretation, etc; History; Aufsatzsammlung